Становлення та розвиток кафедри конституційного права на юридичному факультеті Львівського університету - Гураль, П.; Бойко, І.; Hural, P.; Boyko, I (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті висвітлено особливості становлення та розвитку кафедри конституційного права на юридичному факультеті Львівського університету. Значну увагу зосереджено також на характеристиці становлення та розвитку наукової школи конституційного права, наукових здобутків провідних вчених-правознавців в галузі конституційного права Львівського університету. Історичним результатом розвитку кафедри конституційного права у Львівському університеті є створення наукової школи конституційного права, здатної відповідати вимогам і викликам часу, навчати і виховувати, формувати професійне юридичне середовище, необхідне для утвердження правової держави в Україні. The article is devoted to the analysis of establishment and development stages of the Constitutional Law Department at Lviv National University Law Faculty. Special attention is paid to the constitutional law scientific school description; the article describes scientific activities of Law Faculty’s outstanding legal scholars in constitutional law field. The development of scientific knowledge about constitutionalism at the Law Faculty began after 1848, when Austria adopted the first democratic Constitution and regional Constitution for the Kingdom of Galicia and Lodomeria (1850). The article includes the analysis of the department scholars’ works both in the Soviet period as well as in Ukrainian independence period. The department scholars together with scholars and constitutionalists from Poland created Polish-Ukrainian Constitutionalists Club which has been functioning since 2005. Results of scientific research of department’s scholars used in rulemaking activities of state and local authorities. Members of the department were the initiators and experts of drafting of normative-legal acts. The department collaborates with Constitutional Court of Ukraine, the Central Election Commission of Ukraine and other organs of state power and local self-government. The department is actively involved in legislative work as consultants: on the drafting of the Constitution, the Administrative Code, the Regulations of the Parliament of Ukraine, the Laws of Ukraine.
Establishment and Development of Constitutional Law Department at Lviv University Law Faculty
Keywords: кафедра; конституційне право; юридичний факультет; Львівський університет; вчені-правознавці; department; Constitutional Law; Faculty of Law; University of Lviv; scientists and lawyers